2016
DOI: 10.1007/s00442-016-3699-x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and longitudinal clines of phenotypic plasticity in the invasive herb Solidago canadensis in China

Abstract: significantly positively correlated with latitude and temperature seasonality of the populations. In addition, root/shoot ratio and water-use efficiency showed significant variation in plasticity among populations in response to water availability, and plasticities of these two traits were significantly negatively correlated with longitude and positively correlated with precipitation seasonality. The observed geographic clines in plasticity suggest that phenotypic plasticity of S. canadensis may have evolved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 56 publications
6
51
1
Order By: Relevance
“…Our previous study showed that the phenotypic plasticity of S . canadensis is high in response to temperature and water availability [22]. In the present study, we observed strong plasticity of the proline content, intermediate plasticity of the net photosynthetic rate, stomatal conductance and relative chlorophyll content, and relatively weaker plasticity of the transpiration rate and the activity of peroxidase.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our previous study showed that the phenotypic plasticity of S . canadensis is high in response to temperature and water availability [22]. In the present study, we observed strong plasticity of the proline content, intermediate plasticity of the net photosynthetic rate, stomatal conductance and relative chlorophyll content, and relatively weaker plasticity of the transpiration rate and the activity of peroxidase.…”
Section: Discussionsupporting
confidence: 65%
“…Based on growth chamber and greenhouse experiments, we determined that the phenotypic plasticity of S . canadensis may have evolved rapidly in regions with different climatic conditions and might have contributed to the spread of this invasive species [22]. However, we also found that individual plasiticty, not local adaptation, plays an important role in the response of S .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The plasticity of S. canadensis appears to have a significant influence on its invasive success within a new range in China. It is presumed that the rapid spread of non‐native S. canadensis is related to the rapidly evolving phenotypic plasticity in regions with different climatic conditions (Li, Du, Guan, Yu, & van Kleunen, ). The results of other studies have proved that plasticity in S. canadensis plays a central role in shade adaptation (Du, Liu, Yan, Li, & Li, ) and salt tolerance (Li, Liu, Yan, & Du, ).…”
Section: Introductionmentioning
confidence: 99%
“…The low viability of the SW population specially at the 18L:6D photoperiod may arise from photoperiod‐induced disruption of the circadian system due to the higher plasticity in this northern population (Liu & Zhao, ). Clinal variation in phenotypic plasticity is observed in many organisms, and this might be explained by higher fluctuations in environmental conditions at northern latitudes (Li, Du, Guan, Yu, & van Kleunen, ; Mathur & Schmidt, ; Molina‐Montenegro & Naya, ). A reduction of viability in response to day length has been observed in D. melanogaster , where a long photoperiod reduced survival (Vaiserman et al, ).…”
Section: Discussionmentioning
confidence: 99%